Influence of Test Environment, Age, Sex, and Sport on Baseline Computerized Neurocognitive Test Performance. Issue 13 (November 2019) - French, Jonathan; Huber, Patrick; McShane, Joseph; Holland, Cyndi L.; Elbin, Robert J.; Kontos, Anthony P.
Background: Baseline computerized testing is a common component of concussion assessments, and the testing environment has been suggested to influence test performance and validity. Purpose: To compare concussion baseline computerized neurocognitive test performance and validity among adolescent athletes based on testing environment (group, individual), age group (10-12, 13-15, 16-18 years), sex (male, female), and sport type (collision/combat, contact, noncontact). Study Design: Cohort study; Level of evidence, 3. Methods: Through a concussion community outreach program, participants completed baseline computerized neurocognitive testing using Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT). A total of 2845 athletes aged 10 to 18 years completed the baseline assessment. A total of 2241 (79%) athletes completed baseline testing in a group environment, and 604 (21%) completed testing in an individual environment. A random subsample of 500 athletes from each group was selected for statistical comparison. Results: No significant differences were supported in baseline computerized neurocognitive test performance between the group and individual administration environments. Test validity was statistically similar across testing environment, age group, and sex. However, patients of older age (16-18 years), female sex, and collision/combat and contact sports performed better on ImPACT. There were differences in total symptom severity scores ( t = 2.19, df = 998, P = .03), with participants in the group testing environment reporting lower total symptom severity scores than those in the individual testing environment. The rates of invalid tests were low across all age groups, averaging from 4.0% in the 10- to 12-year age group to 4.8% in the 13- to 15-year age group. Conclusion: The findings indicated that concussion baseline neurocognitive test performance is similar when administered in group and individual testing environments. However, differences based on age group, sex, and sport type should be considered when interpreting baseline computerized neurocognitive test scores. The finding of higher symptom scores in older adolescents in the individual testing environment suggests that they may be less forthcoming about symptoms in a group setting.